Вибродиагностика ГПА на КС "Ромненская" - Игуменцев, Евгений Александрович; Олянич, Михаил Владимирович; Прокопенко, Елена Александровна (НТУ "ХПИ", 2010)
Results of experimental researches by vibrocondition’s definition of gas pumping units are presented. The method is based on the spectral analysis of mechanical fluctuations of machine by Fure fast transformation, i.e. their decomposition on frequency components in narrow strips of frequencies. Monitoring of mechanical fluctuations of GPU is spent by means of stationary systems of the vibrocontrol and by periodic vibroinspections. The stationary systems of vibrocontrol have a number advantages, that consist in continuous process of reception and processing of the information.
Vibrodiagnostics of GPU at CS "Zenkov"
Keywords: техника микропроцессорная; колебания механические; компрессор; турбина; давление высокое; давление низкое; камера сгорания